Surgical Management in Primary Congenital Glaucoma: Four Debates - Ta C. Chang; Kara M. Cavuoto (Journal of Ophthalmology)
Primary congenital glaucoma is a worldwide diagnostic and therapeutic challenge. Although medical management is often a temporizing measure, early surgical intervention is the definitive treatment. As the abundance of surgical treatment options continues to expand, the authors will compare and contrast the available options and attempt to provide a consensus on surgical management.